Penegakan Hukum Terhadap Pelaku Usaha Yang Melakukan Kegiatan Usaha Pertambangan Tanpa Izin Usaha Pertambangan - Jikri Sinurat; Rizkan Zulyadi; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to analyze the urgency of criminal prosecution of perpetrators who carry out mining business activities without a business license, law enforcement in decision Number: 517/Pid.B/2021/PN.Lbp regarding criminal acts of mining without a business license, and the factors that cause the occurrence of criminal acts. mining crime without a business license in Deli Serdang Regency. The type of research used is normative legal research supported by field data through interviews with investigators at the Medan Metropolitan Police. Data analysis in this study was carried out by selecting secondary data from library research and field research data analyzed qualitatively. The results of this study are, the urgency of criminalizing business actors who carry out mining businesses without a permit in Indonesia, namely to avenge criminals' mistakes is also intended to protect the public, by creating order in carrying out mining business activities. Law enforcement against business actors who carry out mining business without a mining business permit in decision Number: 517/Pid.B/2021/PN.Lbp is not optimal and does not reflect a sense of justice. Factors causing the occurrence of cases of mining without a mining business permit in Deli Serdang Regency are divided into 2 (two), namely, internal factors and external factors. Internal factors consist of educational factors and economic factors. On external factors due to the lack of socialization related to mining business licenses and the complicated management of mining business permits.